Seroprevalence of Hepatitis B infection among pregnant women in South India - Rajendiran, Sathiyakala; Gopalan, Ushadevi; Jayakumar, Karthika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Vertical transmission of infection from mother to infants is a very important route of transmission of hepatitis B virus. Hepatitis B virus infection in pregnant women usually goes undetected. The hepatitis B surface antigen in serum is the first seromarker to indicate active HBV infection. This study was done to determine the seroprevalence of HBsAg in healthy asymptomatic antenatal women. Methods: It was a hospital based study over a period of two years. A total of 1282 antenatal patients were tested for hepatitis B surface antigen. Results: The prevalence rate of HBsAg was found to be 1.01 %( 13 positive out of 1282 cases). Highest prevalence was in age group 26-30(46%) followed by age group 31-35(30.8%) followed by age group 20-25 yrs (23.1%). Conclusions: Screening of all pregnant women for HBV irrespective of risk factors will reduce the prevalence and risks of HBV infection.